Educational Robotics for Special Needs Students: Teachers' Perspectives on Pre-service Training - Francesco Agrusti; Gianmarco Bonavolontà (LED Edizioni Universitarie, 2022)
Since the introduction of LOGO by Seymour Papert in 1980 and the constructivist theories, after the teaching machines of Skinner, technology, robots and robotics activities have been viewed as effective educational tools. Multiple studies have demonstrated that robotics is a valuable device for special education students too. The present study is part of a particularly novel and challenging trend of research that intends to fill a knowledge gap regarding the perspectives and concerns of learning support teachers on educational robotics. Particularly by questioning teachers who have not received training in the use of educational robotics. In this exploratory study, 125 Italian pre-service learning support teachers were surveyed at the end or during their course specialization to determine their awareness and comprehension of educational robotics usage with students with special needs. The survey reveals that support teachers are not adequately trained to use educational robotics and that they are generally unfamiliar with it and they rarely employ it.